Rule of law, legal culture, education and academic integrity (Bulletin of Kharkiv National University of Internal Affairs, 2022)
Comparing the 2021 Rule of Law Index, 2021 Legatum Prosperity Index, 2021 Education Rankings by Country, 2021 Times Higher Education, 2021 QS World University Rankings has demonstrated that there is a clear correlation between adherence to the rule of law in the state and the legal culture, education and academic integrity. It is proved that the higher the level of adherence to the rule of law, the higher is the level of legal culture and, accordingly, the level of quality of education and observance of academic integrity.The issues of academic integrity are issues of each country, but the factors influencing academic integrity differ significantly between countries, between different regions, and depending on cultural values. Cultural differences also affect the perception of academic integrity in the world.It is noted that there are several problems with observance of the academic integrity in Ukraine. The attitude to the issues of academic integrity in Ukraine directly depends on the ethical principles and values in society and legal culture.It is concluded that the implementation of academic integrity values requires changes in the system of education and scientific activity in Ukraine. The academic community must be a true advocate of academic integrity and actively strive for its implementation in the everyday institutional life of its members. Universities, faculties and teachers have a significant role to play in communication, strengthening and securing values of academic integrity and policy of the educational institution, academic culture and legal culture in general.Today it is important for Ukrainian institutions not only to create policies, procedures and rules in the field of academic integrity but also to introduce them into the everyday life of the such institution, to constantly improve them, to form academic culture, legal culture and respect for the rule of law.